PENINGKATAN HASIL BELAJAR IPS MELALUI STRATEGI INQUIRY DISCOVERY LEARNING DI KELAS IV SDN KECAMATAN CIKARANG UTARA KABUPATEN BEKASI - Masitoh, Siti (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: Research is based on the low the results and learning and motivation students fourth grade land waluya 01 through the application of learning model inquiry discovery learning thematic and judgment santifik with a focus subjects science social matter identify the tourist destinations through the activities of read maps. To increase yields of student learning writer do research through motede action research, by steps of, planning, the implementation of the, observation, and reflection through steps siklus-siklus improvement where every cycle done researchers done three times the meeting except pre cycle with the object repair processes are learning, study results, and motivation and a studied attitude students. Improvement learning done with stage pra-siklus with these study results student average students only 62, The average score on cycle I increased by 64, and the more increase in cycle II with an average achievement of 75 study results or as much as. 78 percent of students be completed of learning. The conclusions of this research is the application of model inquiry discovery in learning social class in the class iv can improve the results and learning students, reduce services learning did as teachers and can as input for fellow has another in efforts to improve study results students. Keywords: inquiry discovery learning Social Studies, the results and the motivation to studyAbtrak: Penelitian ini didasarkan pada rendahnya hasil dan proses belajar serta motivasi siswa kelas IV SD Negeri Waluya 01 melalui penerapan model pembelajaran Inquiry Discovery pembelajaran tematik dan penilaian santifik dengan fokus mata pelajaran Ilmu Pengetahuan Sosial. Untuk meningkatkan hasil belajar siswa penulis melakukan penelitian melalui motede action research, dengan langkah-langkah berupa, perencanaan, pelaksanaan, observasi, dan refleksi melalui tahapan-tahapan siklus-siklus perbaikan dimana setiap siklus yang dilakukan peneliti dilakukan sebanyak tiga kali pertemuan kecuali pra siklus dengan objek perbaikan proses pembelajaran, hasil belajar, dan motivasi serta sikap belajar siswa. Perbaikan pembelajaran dilakukan dengan tahapan pra-siklus dengan capaian hasil belajar rata-rata siswa siswa hanya 62 perolehan nilai rata-rata pada siklus I mengalami peningkatan sebesar 64 dan makin meningkat pada siklus II dengan rata-rata pencapaian hasil belajar sebesar 75 atau sebanyak 78 % siswa tuntas belajarnya. Kesimpulan dari penelitian ini adalah penerapan model inquiry Discovery pada pembelajaran Ilmu Pengetahuan Sosial di kelas IV dapat memperbaiki hasil dan proses belajar siswa, mereduksi layanan pembelajaran yang dilakukan guru serta dapat menjadi masukan bagi rekan sejawat lain dalam upaya meningkatkan hasil belajar siswa.Kata kunci : Inquiry Discovery, Pembelajaran IPS, Hasil dan Motivasi Belajar